Literasi Keuangan Melalui Gerakan Gemar Menabung Sejak Dini di Kalangan Sekolah Pinggiran Sriwijaya - Marissa, Feny; Deassy Apriani; Nazeli Adnan (UNIB Press, 2024)
This activity aims to raise awareness and provide an understanding about financial literacy through early savings activities for the children in Sekolah Pinggiran Sriwijaya so they can improve the quality of life and walfare in the future. The implementation method for this activity is carried out in three stages that are 1)discussion; 2)tutorial and; 3)practice. The results showed that children can understand about importance of saving from an early age to adopt frugal lifestyle for a better future. Furthermore, children have succeeded in setting aside their pocket money to be saved ini piggy banks which they have decorated with their own creativity.